2001
DOI: 10.1073/pnas.091100898
|View full text |Cite|
|
Sign up to set email alerts
|

Tryptophan zippers: Stable, monomeric β-hairpins

Abstract: A structural motif, the tryptophan zipper (trpzip), greatly stabilizes the β-hairpin conformation in short peptides. Peptides (12 or 16 aa in length) with four different turn sequences are monomeric and fold cooperatively in water, as has been observed previously for some hairpin peptides. However, the folding free energies of the trpzips exceed substantially those of all previously reported β-hairpins and even those of some larger designed proteins. NMR structures of three of the trpzip peptides reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

79
1,144
4
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 713 publications
(1,230 citation statements)
references
References 39 publications
79
1,144
4
3
Order By: Relevance
“…Studies of isolated, water-soluble -hairpins can provide valuable insight into properties of -sheet structure and folding since -hairpins are considered to act as possible nucleation sites for protein folding. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Additionally, their detailed structural interactions can be relevant in developing an understanding of the mechanism for forming various -sheet structures such as found in many (amyloid-like) neurodegenerative diseases in which protein aggregation is an important pathology. [15][16][17][18] During the past decade, there have been many reports discussing de novo designed, water-soluble -hairpin peptide systems, as well documented in several reviews.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of isolated, water-soluble -hairpins can provide valuable insight into properties of -sheet structure and folding since -hairpins are considered to act as possible nucleation sites for protein folding. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Additionally, their detailed structural interactions can be relevant in developing an understanding of the mechanism for forming various -sheet structures such as found in many (amyloid-like) neurodegenerative diseases in which protein aggregation is an important pathology. [15][16][17][18] During the past decade, there have been many reports discussing de novo designed, water-soluble -hairpin peptide systems, as well documented in several reviews.…”
mentioning
confidence: 99%
“…Trpzip has been reported to be the smallest peptide sequence that has a tertiary structure without disulfide bonds or metal binding. 1 The folding of -hairpins has been proposed to be initiated either by a sequence of residues with high propensities to form turn structures which then bring the -strands together ("zipping" mechanism) 35 or by nonbonded interactions between opposing residues on the strands that lead to hydrophobic collapse and enable cross-strand hydrogen bond formation and subsequent turn formation. 10 Trpzip is an excellent model for study of such a hydrophobic collapse, which has been shown to contribute to its structural stability and the heterogeneity of its folding dynamics.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Trpzip-I molecule, a 12-residue small peptide, forms a stable β-hairpin structure in aqueous solution [11]. Moreover, NMR data of that molecule is unusually of high quality for a short peptide indicating a highly ordered structure.…”
Section: Introductionmentioning
confidence: 99%